The Effect of Mycorrhiza on Nitrogen and Phosphorus Requirement of Nursery Grown Eucalyptus - Djunita, Tengku Sabrina (1998)
Eucalyptus is a potential forest species which is fast growing and has multipurpose uses. The forest plantation of PT. Inti Indorayon Utama in Indonesia faces serious problem of sending survival during transplanting. Furthermore, the budget for fertilizer in the nursery is also very expensive. The objective of this study therefore was to examine the effects of mycorrhiza application on nitrogen and phosphorus requirement of nursery grown eucalyptus. The study consisted of three components. The survey examined the occurrence of mycorrhizae in several plantation sectors. The effectivity trial evaluated the effectiveness of indigenous versus commercially produced mycorrhiza inoculum. The nursery trial examined the effect of selected mycorrhiza on nitrogen and phosphorus requirement of eucalyptus seedlings. Results from the survey showed that both ectomycorrhiza and arbuscular mycorrhiza were present in the almost all plantation sectors examined. plant age increased AM spore number, root colonization and presence of EM. Plantation management practices and the amount of soil organic matter in the forest were factors that contribute to the decrease in AM spore number under the young eucalyptus stands. The combined effect of spore number and several soil properties (Cu, Zn and pH) as well as the stage of eucalyptus stands affect percentage AM root colonization. The results from the effectivity study found that indigenous inoculum from Habinsaran was the most effective. However, its effectivity was lower than the commercially produced mycorrhiza. The results from the nursery study showed that mycorrhiza was able to increase seedling height, while reducing the amount of phosphorus fertilizer applied to the plants. However, mycorrhiza was not able to replace the nitrogen function in seedling growth. Application of combined indigenous with the commercial mycorrhiza inoculum gave the best overall seedlings ,growth compared to individual mycorrbi2'a inoculum (indigenous or commercial). The amount of N and P fertilizers applied also influenced the mycorrbiza role in increasing seedling growth. In conclusion growth of Eucalyptus seedlings was found to be significantly (p S; 0.05) affected by both mycorrhiza and fertilizer factors.